1) 27B^2 + 108B + 108 = 27 * ( B^2 + 4B + 4 ) = 27 * ( B + 2) * ( B + 2 ) 2) ( 27 *( B + 2)^2 ) : ( 6 / ( B + 3 ) ) = ( 27 * ( B + 2)^2 ) * ( B + 3 ) ) / 6 = = 4,5 * ( B + 3 ) * ( B + 2)^2 ------------------------------------------------------------------------------------B = - 4/9 1) B + 3 - 4/9 + 3 = - 4/9 + 27/9 = 23/9 2) ( B + 2)^2 ( - 4/9 + 2)^2 = ( - 4/9 + 18/9 )^2 = ( 14/9)^2 = 196/81 3) 4,5 * 23/9 * 196/81 = 9/2 * 23/9 * 196/81 = 4508/162= 2254/81 = 27 67/81--------------------------------------------------------------------------------------Ответ 27 целых 67/81